A hut too far: history of the Argentine Ventimiglia shelter on Peter I Øy - Fontana, Pablo Gabriel (Polar Research, 2018)
This paper addresses the barely known history of an Argentine Antarctic hut: the Teniente Luis Ventimiglia hut, installed by the Argentine Antarctic Institute on Peter I Øy (Peter I Island) in March 1971. In examining the history of the only Argentine Antarctic facility outside of the Argentine Antarctic Sector, this article describes the reasons behind the establishment of the hut and the scientific work that took place there as well as previous Argentine expeditions to Peter I.
Keywords: Argentina; Peter I. Øy; ekspedisjoner; forskningsstasjoner; meteorologi; oseanografi

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Changes at Peter I Øy - Headland, Robert K (Polar Research, 2007)
Peter I Øy, a remote Norwegian territory, is one of the most rarely visited of the peri-Antarctic islands. Since the last Norwegian research visit, in 1987, approximately 10 tourist ships have been to the island, and about half of these have made landings. Where practical, reports have been sent to the Norwegian Polar Institute and other interested parties. I have made five visits, landing during four of them, while employed by Quark Expeditions to lecture on Antarctic history and geography aboard Kapitan Khlebnikov . My most recent visit, on 21 November 2006, demonstrated the continual geological erosion of the coast. In 2004 at Pingvinholet there was a splendid triple natural arch: the outer arch was formed by black basaltic deposits, and the inner one was capped by a stratum of red oxidized larva. The third arch was the result of a basalt flake slipping and propping itself against the middle column. The sea penetrated through all three arches so that it would have been possible, although reckless, to take a small boat through the largest of them. In late 2006, while sailing from South America to New Zealand near the Antarctic coast, I noted the entire inner section had collapsed. Only one large arch now remains and this no longer admits the sea. The collapse of both the cap of red larva and supporting pillar has formed a pile of rubble several metres above the sea.
Keywords: Peter I. Øy; geologi; turisme

Quantitative analysis of soft-bottom molluscs in the Bellingshausen Sea and around Peter I Island - Troncoso, Jesús S; Aldea, Cristian; Arnaud, Patrick; Ramos, Ana; García, Francisco (Polar Research, 2007)
Macrobenthic soft-bottom molluscs were sampled in 30 stations located in the Bellingshausen Sea at depths ranging from 90 to 3304 m. The samples were collected using a quantitative grab box-corer during the cruises BENTART 03, from 24 January to 3 March 2003, and BENTART 06, from 2 January to 16 February 2006. Molluscs represent 1074 specimens belonging to 62 species of Polyplacophora, Gastropoda, Bivalvia and Scaphopoda. The bivalve Cyamiocardium denticulatum was the most abundant species (448 specimens). The abundance per station varied between 1 and 446 specimens. The Shannon–Wiener diversity index ranged between one specimen and 2.36, the Pielou evenness index ranged between 0.00 and 1 and species richness ranged from 1 to 14 species. Diversity showed great variations at different stations. After multivariate analysis (cluster analysis and nonmetrical multidimensional scaling) based on Bray–Curtis similarities, we were able to separate two principal clusters. The first cluster groups together species from shallower bottoms near Peter I Island and the Antarctic Peninsula, and the second cluster groups together species from deeper bottoms in the Bellingshausen Sea. The combination of environmental variables with the highest correlations with faunistic data was that of depth and coarse sand at the surface.
Keywords: Peter I. Øy; Sørishavet; bløtdyr; marin biologi; marine økosystemer; mollusker; oseanografi

Historien om skuta Vesleper - Olsen, Else Mehren (Follominne: årbok, 2001)
Keywords: Antarktis; Bouvetøya; Peter I. Øy; Sørishavet; ekspedisjoner; historie; hvalfangst